Patient reported outcomes for the detection, quantification and evaluation of chronic obstructive pulmonary disease exacerbations - Mackay,AJ; Kostikas,K; Murray,L; Martinez,FJ; Miravitlles,M; Donaldson,G; Banerji,D; Patalano,F; Wedzicha,JA (American Journal of Respiratory and Critical Care Medicine, 2018)
An exacerbation of Chronic Obstructive Pulmonary Disease (COPD) is an acute worsening of respiratory symptoms, accompanied by a variable degree of physiological deterioration. The traditional assessment of an exacerbation consists of the reporting of symptoms directly by the patient to a clinician and subsequent clinical assessment. It would be valuable to also gather symptom reports directly from patients and thus patient-reported outcome (PRO) tools should be ideally suited to the evaluation of COPD exacerbations. However, most pharmaceutical and large academic-sponsored studies have used a healthcare resource utilization definition alone based on sustained worsening of a patient's condition from the stable state that requires a change in regular medication. This review explores the use of PROs for the detection, quantification, and evaluation of COPD exacerbations. It examines symptom diary cards as exacerbation detection tools and their evolution into electronic diaries used in pharmaceutical trials. This paper also describes the development of specifically designed PROs that have been used in exacerbation settings, focusing on the Exacerbations and Symptoms in COPD (ESCO) e-Diary, EXAcerbations of Chronic Obstructive Pulmonary Disease Tool (EXACT®), COPD Assessment Test™ (CAT) and Chronic Respiratory Disease Questionnaire (CRQ), highlighting the strengths and weaknesses of these instruments. We describe the effectiveness of these tools to enhance exacerbation reporting, quantify exacerbation characteristics, including the frequency, duration, and severity of events, and evaluate the outcome. We also explore the potential use of PROs in future studies to discriminate the effect of therapies on different exacerbation phenotypes and thus enhance personalized therapeutic approaches.